Śuklayajurvedīyānām āhnikam : prātaḥprabhr̥tisāyāntaṃ sāyādiprātatantataḥ kartavyaṃ nityakarma - Daivajña, Bālabhaṭṭa ("Śrīveṅkaṭeśvara" (Sṭīm) Yantrālaye, 1923)
Manual of Hindu ritualistic practices according to the Mādhyandina rencension of the Yajurveda.